ROLE OF SERVICE QUALITY PT. ULTRAJAYA MILK INDUSTRY CO TBK EAST JAKARTA TO CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE - Sanusi Silitonga, Eddy (Dinasti Publisher, 2021)
The research objective to be achieved is to determine the effect of service quality on customer loyalty through customer satisfaction. PT. Ultrajaya Milk Industry Co Tbk, East Jakarta. This research uses quantitative methods. The population in this study were customers of Ultrajaya Milk Industry Co Tbk, East Jakarta. The sampling technique uses the incidental sampling technique. Before testing the hypothesis, the data instrument is tested; first, the data analysis method uses simple linear regression and path analysis. The research results can be concluded as follows: 1). Service quality has a positive and significant effect directly on customer loyalty. 2). Customer satisfaction has a positive and significant effect directly on customer loyalty. 3). Service quality has a positive and significant effect directly on customer loyalty. 4). Service quality has an indirect positive and significant effect on customer loyalty through customer satisfaction. PT. Ultrajaya Milk Industry Co Tbk, East Jakarta.